ANALISIS KAPASITAS POMPA KOLAM RETENSI MUKTIHARJO KIDUL PEDURUNGAN SEMARANG - Azzahra, Anissa Aufa; Rivana, Hesti Almaria; Niam, Moh. Faiqun; Sentani, Ari (Jurnal Ilmiah Sultan Agung, 2024)
This study aims to analyze maximum rainfall, peak discharge, and retention pond volume in managing river water during maximum discharge events. The methods used include calculating rainfall using the Thiessen Polygon Method, analyzing peak discharge with the Nakayasu Synthetic Unit Hydrograph (HSS) Method, and conducting a hydraulic analysis of retention pond volume. Rainfall data were collected from three rain gauge stations, and probability distribution testing was conducted to determine data distribution. The results show a maximum rainfall of 107.973 mm and a peak flood discharge of 12.963 m³/s with a peak time of 2.865 hours. The hydraulic analysis indicates that with a pump capacity of 5 m³/s, the required retention pond volume is 301,680 m³, while with a pump capacity of 10 m³/s, the required retention pond volume is 233,040 m³.Kata Kunci: Curah Hujan Maksimum, Kolam Retensi, HSS Nakayasu, Metode Poligon Thiessen, Analisis Hidrolika.